2012
DOI: 10.1016/j.humimm.2011.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Favorable effects of alemtuzumab on allospecific regulatory T-cell generation

Abstract: We studied the effects of alemtuzumab on T-regulatory cells (Tregs) during alloactivation, first by differences in depletion of various naive versus alloactivated cell subsets in peripheral blood of healthy volunteers, then by adding serial concentrations to human leukocyte antigen (HLA)–DR–matched and –mismatched responding and stimulating cells in mixed lymphocyte reaction (MLR). Lymphoproliferation inhibition and the development of proliferating carboxyfluorescein succinimidyl ester (CFSE)–diluted CD4+CD25h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…4B and C). The percentage of CD127 − CD25 + FOXP3 + total Tregs in the medium controls without HBIG comprised 10–40% of the CD4 + cells in the proliferating fraction depending on individual MLR combinations in each experiment, with the percentage of CD127 − CD25 High FOXP3 + nTregs being slightly lower, also consistent with previous observations [1113]. There was no significant effect of HBIG in any concentration on the generation of these Tregs in culture over that of media controls, in contrast to other immunoregulatory agents tested previously [12,13].…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…4B and C). The percentage of CD127 − CD25 + FOXP3 + total Tregs in the medium controls without HBIG comprised 10–40% of the CD4 + cells in the proliferating fraction depending on individual MLR combinations in each experiment, with the percentage of CD127 − CD25 High FOXP3 + nTregs being slightly lower, also consistent with previous observations [1113]. There was no significant effect of HBIG in any concentration on the generation of these Tregs in culture over that of media controls, in contrast to other immunoregulatory agents tested previously [12,13].…”
Section: Resultssupporting
confidence: 91%
“…4A. As previously reported with other agents [1113], we tested the influence of HBIG on the development of newly generated Tregs in the proliferating fraction (Fig. 4B and C).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…The mechanism responsible for the initial increase in Treg is not understood, but de novo generation was suggested and could be explained by the induction of Treg in vivo (22). In vitro studies of Treg proliferation have shown that Treg expand preferentially in allogeneic MLR in the presence of alemtuzumab (23). However, in a similar study, incubation of human PBMC with anti-thymocyte globulin was associated with Treg expansion whereas, by contrast, alemtuzumab depleted CD25 + Treg (17).…”
Section: Discussionmentioning
confidence: 99%